The Tri-People Relationship and the Peace Process in Mindanao - R. Rodil, B. (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper is divided into three parts. Part One is on the historical back ground of the tri-people relationship; Part Two covers the GRP-MNLF peace process; and Part Three focuses on the basic considerations in advocacy for peace and development. Tri-people refers to the three broad segments of the population of Mindanao and the Sulu archipelago namely, the Lumad ethno-linguistic groups, the Moro communities and the generally Christian or migrant inhabitants. Given the history of Mindanao wherein the indigenous inhabitants became displaced, discriminated against and reduced to the status of minorities in their own ancestral lands and the migrants became the dominant popula tion, we have now reached a point when it is no longer rational to think of peace and development in the region without seriously considering how the same may be mutually beneficial to all concerned. The tri-people approach is presented here as such a strategy. This is the way to a common vision and a Common destiny.